The contribution of Tomas Maldonado to the scientific approach to design at the beginning of computational era THE CASE OF THE HFG OF ULM - Neves, Isabel Clara (2015)
ABSTRACT: Nowadays the use of computational design processes in architecture is a common practice which is currently recovering a set of theories connected to computer science developed in the 60`s and 70`s. Back then, such pioneering experiences were carried out by an interest in employing scientific principles and methodologies in architectural design, which, with the help of computers, were developed in Research Centres mainly located in the USA and the UK. Looking into this period, this paper investigates the relevance of the German design school of the Hochschule für Gestaltung of Ulm to the birth of computation in architecture. Even though there were no computers in the school, this paper argues that the innovative pedagogies introduced by a group of distinct professors built clear foundations that can be understood as being at the basis of further computational approaches in architecture. This paper focuses on the remarkable work done by Tomas Maldonado. His contribution was paramount in the emergence of analogical ways of computer design thinking. This analysis ultimately wants to emphasize how the HfG Ulm’s role and its scientific approach have paved the way for the onset of the computational era in architecture.